A pooled RP/SP mode, route and destination choice model to investigate mode and user-type effects in the value of travel time savings. (June 2019) - Schmid, Basil; Jokubauskaite, Simona; Aschauer, Florian; Peer, Stefanie; Hössinger, Reinhard; Gerike, Regine; Jara-Diaz, Sergio R.; Axhausen, Kay W.
Abstract: Being of great importance for transportation policy appraisals, we investigate mode and user-type effects in the value of travel time savings (VTTS) using a pooled RP/SP Mixed Logit modeling approach for mode, route and destination choice data. For a representative sample of Austrian workers, our analysis reveals population-weighted median VTTS estimates for car (12.3 Euro/h), public transportation (PT; 8.1 Euro/h), bike (11.7 Euro/h) and walk (10.2 Euro/h). Considering only those respondents who have used car and PT in the observation period (and thus are familiar with both modes), we find that four user characteristics are able to decompose this substantial difference in median VTTS between car and PT (i.e. the total mode effect) of about 4.9 Euro/h: Posterior means of individual and mode-specific VTTS distributions reveal a reduced mode effect for high income (4.6 Euro/h), female (4.5 Euro/h), low educated (4.3 Euro/h) and urban (3.0 Euro/h) user groups. Our results indicate that in the case of Austrian workers, characteristics of the mode are more important than characteristics of the users, and that the travel time spent in PT is valued less than in a car for all investigated user groups.